Hubungan Antara Kekuatan Otot Quadriceps Femoris Dengan Kecepatan Berjalan Pada Lanjut Usia di Posyandu Dahlia Boyolali - Anggoro, Arif, Yulisna Mutia Sari, SST., Ft., M.Sc. (GRS) (2014)
ABSTRACT The Correlation between strength Quadriceps Femoris to speed walk of Dahlia Posyandu elderly in Boyolali Physiotherapy Majors Hygiene Faculty Muhammadiyah University of Surakarta Arif Suryo Anggoro J 120 110 006 (Guided by Yulisna Mutia Sari, SSt.FT,M.Sc (GRS) and Umi Budi Rahayu, SSTFT, M.Kes) (Consisted of 43pages, V chapter, 8 tables, 13 pictures, 8enclosures) Someone to be an elderly will have health problems like slower speed when they are walking. The walk speed of the elderly can influenced by strength Quadriceps Femoris decreases force Quadriceps Femoris muscle to more long time for a walk. The same thing occurs in posyandu dahlia which they are decline Quadriceps Femoris Objective to know correlation between strength quadriceps femoris to speed walk of Dahlia Posyandu elderly in Boyolali. This study done in May 2015. method study was observational research with cross sectional approach. The sample were 39 members of Dahlia elderly posyandu. Taking sample used total sampling. Instrument research in muscular power with spring balance in a unit of kilograms. Speed of walking test use ten meters walk test with measuring seconds .Data analysis using the rank spearman . The research results show 17 respondents (43,6 %) with muscular strength of 16-20 kg, and speed walking on 6 meters mostly during 3-3.9 second. Result rank spearman test obtained value rtest = -0.516 p = 0,001. The conclusion there was correlation between quadriceps femoris to speed walk of Dahlia Posyandu elderly in Surakarta. more strength muscular quardriceps femoris more faster time to walk in 6 meters Keyword: Quardriceps Femoris, speed walk, elderly